Community Empowerment in Transforming Household and Agricultural Waste into Valuable Products towards the Green Village Concept - Arita Dewi Nugrahini; Makhmudun Ainuri; Wagiman Wagiman; Rosa Amalia; Surani Hasanati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
It is essential to manage waste in an integrated manner, beginning at the domestic and village levels. In fact, there are still a significant number of residents who throw trash carelessly. Jurangjero village, a village in Klaten Regency, Central Java, is an example of a village that does not adequately manage its waste. In addition, the village has agricultural waste issues that require optimal utilization, including rice straw. This community service program aims to increase public awareness of organic and inorganic domestic waste management and agricultural waste management so that they can be applied appropriately to the concept of the green village. The program’s methods included field observations, waste management outreach, and training. The training included the creation of organic fertilizers, eco-bricks, plastic waste containers, and straw paper. Farmer groups and farmer women’s groups have gained an understanding of the management of domestic organic waste into organic fertilizer and compost as a result of the outreach and training activities. Karangtaruna has also gained an understanding of inorganic waste management by applying the recycling concept, which entails transforming plastic refuse into plastic pots and ecobricks. They have also grasped the production of economically valuable art paper from rice stalks. The descriptive analysis revealed that the average pre-test and posttest scores were 55.58 and 76.67, respectively. Based on these findings, it can be concluded that this community service program has increased residents’ knowledge of managing domestic and agricultural waste to create valuable products. The support of the village administration is required for sustainable waste management and the continuation of empowerment initiatives.